Value of bronchoscopy in the diagnosis of sputum smear negative pulmonary tuberculosis - Peposhi, Ilir Pajazit; Kapisyzi, Perlat Qazim; Hafizi, Hasan Sulejman; Bala, Silvana Abdi; Nuredini, Ornela Gani (International Journal of Research in Medical Sciences, 2017)
Background: Bronchoscopy has been found to be applicable in diagnosing suspects of pulmonary TB which have no sputum or sputum smear negative for acid fast bacilli. Additionally, it is helpful in the diagnosis of endobronchial tuberculosis, allowing early detection of broncho stenosis. Methods: A prospective study, where bronchoscopy was conducted in 167 patients with acid-fast bacillus sputum smear negative. The average age of the patients was 44.1±19.4, from age 15 to 87 years old, higher frequency in age from 20-40 years old and 55-64 years old. Results: From 167 patients in the study, endoscopic presentation resulted: normal in 7 (4.2%) cases, bronchitis - 60 (35.9%) cases, oedematous-hyperaemic -62 (37.1%) cases, caseous inflammation - 7 (4.2%) cases, ulcerative lesions - 3 (1.8%) cases, tumoral lesions - 21 (12.6%) cases and fibrous stenotic changes in 7 (4.2%) patients. From 44 (26.3%) patients to whom was obtained biopsy, the histological examination has resulted: 24 (54.5%) cases with TB granuloma, 14 (31.8%) - epithelioid granulomas and in 6 (13.6%) cases resulted non-specific inflammation. The examination of bronchial washing for acid-fast bacillus smear concluded the diagnosis in 40.4% of cases, the examination for acid-fast bacillus smear collected after diagnostic FBS has been decisive in 53.9% of cases. The examination for acid-fast bacillus culture resulted positive in 70.5% of bronchial washing and in 61.2% of sputum collected after FBS. Conclusions: Fibreoptic bronchoscopy plays the key role to the patients with suspected tuberculosis which are acid-fast bacillus smear negative or that have no sputum.